Safety nets in Bangladesh: Which form of transfer is most beneficial? Operational performance of the transfer modality research initiative - Ahmed, Akhter; Sraboni, Esha; Shaba, Fiona K. (International Food Policy Research Institute, 2014)
The overall objective of the Transfer Modality Research Initiative (TMRI) is to provide evidence that can be used to streamline the social safety net system in Bangladesh, with the goal of improving the food and nutrition security and livelihoods of the very poor in a cost-effective way. The research will inform policymakers which type of program can best improve the income status and food and nutrition security of the poor and thus be a valuable tool to the government as it prepares its social protection strategy.